Risk-based pricing in competitive lending markets - Carola Müller; Ragnar Enger Juelsrud; Henrik Andersen (Norges Bank, 2021)
We use unique data on banks' private risk assessments of corporate borrowers to quantify how competition among banks affect the risk sensitivity of interest rates in the Norwegian credit market. We show that an increase in competition makes corporate lending rates less sensitive to banks' own assessment of borrower risk and this is more pronounced in market segments with higher degree of asymmetric information. Our results are driven by banks with low franchise values, outlining a novel channel of how the competition-fragility nexus can operate.
hdl:11250/2835496
Keywords: G11; G21; G28; 330; Banking competition; market power; risk pricing; financial stability